Liquidity management and profitability: a case study of listed commercial banks in sri lanka - Saraniya, M.; Vinothiny, B.; Sharuga, K.; Sutharsan, J.; Vijithan, S.; Arunprasath, F. (university of Jaffna, 2014)
Management of liquidity has become a crucial issue in today's dynamic competition between banking sector to attain maximum profitability for achieving target and to survival in the competitive world. This study is aimed to identify the liquidity management on profitability of commercial banks in Sri Lanka during the period of 5 years from 2008 to 2012. In Sri Lanka eight banks are listed under Colombo stock exchange (CSE). Hence, out of eight, only five banks are selected for the study purpose as convenience. Correlation and regression analysis were used in the analysis and findings revealed that there is a significant relationship exists between liquidity and profitability among the commercial banks in Sri Lanka. Here Liquidity of bank was measured through the Liquid Assets Ratio (LAR), Current Ratio (CR), Reserve Ratio (RR) and Capacity Ratio(CAR) and profitability was measured by Return on Asset (ROA) and Return on Equity (ROE) Ratios.
Keywords: Liquidity; Liquidity management; Profitability; Colombo stock exchange